PARP inhibitor synthetic lethality in ATM biallelic mutant cancer cell lines is associated with BRCA1/2 and RAD51 downregulation - Muvaffak, Asli; Coleman, Kevin G. (Frontiers in Oncology, 2024)
Background: Ataxia Telangiectasia-Mutated (ATM) kinase is a central regulator of the DNA damage response (DDR) signaling pathway, and its function is critical for the maintenance of genomic stability in cells that coordinate a network of cellular processes, including DNA replication, DNA repair, and cell cycle progression. ATM is frequently mutated in human cancers, and approximately 3% of lung cancers have biallelic mutations in ATM, i.e. including 3.5% of lung adenocarcinomas (LUAD) and 1.4% of lung squamous cell carcinomas (LUSC).Methods: We investigated the potential of targeting the DDR pathway in lung cancer as a potential therapeutic approach. In this context, we examined whether ATM loss is synthetically lethal with niraparib monotherapy. This exploration involved the use of hATM knockout (KO) isogenic cell lines containing hATM homozygous (-/-) and heterozygous (+/-) generated via CRISPR/Cas9 gene knockout technology in DLD-1, a human colorectal adenocarcinoma cell line. Subsequently, we extended our investigation to Non-Small Cell Lung Cancer (NSCLC) Patient Derived Xenograft (PDX) models for further validation of Poly ADP-Ribose Polymerase inhibitor (PARPi) synthetic lethality in ATM mutant NSCLC models.Results: Here, we demonstrated that biallelic hATM deletion (-/-) in DLD-1 impairs homologous recombination (HR) repair function and sensitizes cells to the PARPi, niraparib. Niraparib also caused significant tumor regression in one-third of the NSCLC PDX models harboring deleterious biallelic ATM mutations. Loss of hATM (-/-) was concomitantly associated with low BRCA1 and BRCA2 protein expression in both the hATM (-/-) DLD-1 cell line and PARPi-sensitive ATM mutant NSCLC PDX models, suggesting a downstream effect on the impairment of HR-mediated DNA checkpoint signaling. Further analysis revealed that loss of ATM led to inhibition of phosphorylation of MRN (Mre11-Rad50-NBS1) complex proteins, which are required for ATM-mediated downstream phosphorylation of p53, BRCA1, and CHK2.Taken together, our findings highlight that the synthetic lethality of niraparib in ATMdeficient tumors can be regulated through a subsequent effect on the modulation of BRCA1/2 expression and its effect on HR function.